2014
DOI: 10.1111/dsu.12419
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Mohs Micrographic Surgery Sections Using Full-Field Optical Coherence Tomography: A Pilot Study

Abstract: Malignancy in Mohs sections can correctly be identified or excluded using FF-OCT. Although not ready for clinical use in its current state, FF-OCT has the potential to be incorporated into the Mohs workflow in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The majority of studies identified in this review investigated margin delineation in OCT examination. Six of the 10 studies were STROBE B, three were STROBE C and one was STROBE A (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies identified in this review investigated margin delineation in OCT examination. Six of the 10 studies were STROBE B, three were STROBE C and one was STROBE A (Table ) …”
Section: Resultsmentioning
confidence: 99%
“…The study reports sensitivity, specificity and positive predictive value of 75%, 64% and 61%, respectively, based on 80 images obtained from 20 BCCs with four margins each . Similarly, full‐field (FF)‐OCT, which has a higher resolution than conventional OCT and HD‐OCT, correctly identified two of three BCC tumours when used ex vivo on frozen sections . Of note, all four margins were correctly identified in only 45% of tumours …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition to these limitations, the preparation of frozen sections requires a specialized laboratory set-up and a trained Mohs technician, raising the overall cost of the Mohs surgery and pathology procedure. 4 To overcome the limitations of the frozen sectioning process and provide rapid histopathological evaluation of ex vivo fresh tissue, several optical imaging techniques are being explored, such as confocal mosaicking microscopy, 9,[11][12][13][14][15] fluorescence polarization, 16 multiphoton laser scanning microscopy, 17 fluorescence lifetime imaging, 18 Raman spectroscopy, 19 integrated autofluorescence and Raman scattering microscopy, 20 optical coherence tomography (OCT), 21 full-field OCT, 22 coherent antiStokes Raman scattering microscopy, 23 multimodal spectral imaging, 24 and terahertz spectral imaging. 25,26 Confocal mosaicking microscopy (CMM) is currently the furthest advanced, being implemented and validated in Mohs surgical settings in real time.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to confocal systems, FFOCT further holds the advantage not to require lasers or fast scanning elements; the technique can be integrated in a simple setup. The FFOCT has already been evaluated in the pathology laboratory in various preclinical studies on human skin, 24,25 pulmonary, 26 urologic, 27 and gastrointestinal tissue, 28 retina and cornea, 29,30 and brain. 31 Recently, a preclinical study was performed on breast tissue samples 32 and achieved sensitivity of 92% and specificity of 77%.…”
Section: Introductionmentioning
confidence: 99%